Propuesta de Modelo de Aplicaciones Prácticas de la Curva de Rendimiento Soberana para la Toma de Decisiones de Inversión Financiera - Mora-Díaz, David; Ugalde-Rivera, Armando (Instituto Tecnológico de Costa Rica, 2017)
The present research on the sovereign yield curves was carried out with the purpose of to develop the possible utilities that they give us. It is addressed to students of the Master in Business Administration, so that it can be used as a tool or for a possible extension of it, since the performance curves have other uses, which in this work were not developed by the short time of the Seminar. Within the applications that this curve has developed a case where an international company with operations in several countries was taken, based on the United States Treasury bonds, since they are risk free, a spread was calculated which Is added to the cost of capital that the company has defined. This spread was calculated for several countries in the region and their different values were compared depending on the country where the exercise is desired. We then calculate a weighted average capital cost (CPPC), to use this new capital cost (Ke) and observe the effect that this has on the cost of debt and the differences between each country. Finally, a "real" exercise of a possible investment was made here in Costa Rica, comparing with two countries; Canada and Brazil. The idea is to see how in a country like Brazil where its spread is quite large compared to that of Canada that turns out to have many more attractive bonds than the United States. This shows us a good contrast of where it would be better to invest and we fulfill one of the objectives of this work, practical applications of the yield curve and shows us the importance of following a tool like this one for the investment decision making.
Proyecto de Graduación (Maestría en Administración de Empresas con énfasis en Finanzas) Instituto Tecnológico de Costa Rica. Escuela de Administración de Empresas, 2017.
Keywords: Curva; Rendimiento; Spread; Capital; Costo